(untitled) (Research, Society and Development, 2022)
Promoting an integrated system to measure economic, social and environmental performance is fundamental to assist the management of rural establishments, being able to point out the endogenous potential to achieve sustainable development. This work has as main objective to analyze the sustainable regional development in the Territory of Cariri Oriental Paraibano.The theoretical basis is the work of Agenda 21, Ferreira et. Al. (2012), May (2010), Baroni (2001), Wanderley (2001), Mol (2000), among others. Data were collected in the reports of the municipal departments of agriculture and development, in the report of ptdrs - Territorial Plan for Sustainable Rural Development of The Eastern Cariri, in the documents of the Secretariat of Territorial Development – SDT linked to the Ministry of Agrarian Development - MDA and IBGE. The basic justification is that in recent years the territory has benefited from sustainable development policies, focused on family production, such as Law 11.947/2009 and movements related to sustainable agroecological production. The hypothesis that family farming in the territory resembles employer’s agriculture is validated as production planning is based on the market and not family consumption at the same time that the labor, property and enjoyment of the land has in its essence the family, the activity is verified as a result of the family effort and promoting economic sustainability, environmental equity and social responsibility. The data show that the municipalities bordered by BRs and/or have non-essentially rural activities, have the highest HDI, showing that despite the majority of the labor occupied in the territory is linked to family agriculture, this is not able to generate economic sustainability, despite being the best bet for environmental sustainability.